The Photobook as a Medium for Cultural Communication: Documentary Photography and Bamboo Heritage in Dusun Ngadiprono - Shena Shena; Arindra Karamoy (Center for Southeast Asian Social Studies (CESASS), 2026)
Although bamboo is abundant in Indonesia, it is often undervalued despite its cultural, ecological, and economic potential. This study responds to the need for an effective communication medium to convey the success of the Pasar Papringan revitalization initiative and to increase public awareness of bamboo preservation. The research aimed to design a documentary photography-based photobook titled Napak Tilas: Bambu and to explore an innovative in-situ dissemination strategy, in which the exhibition is presented within the bamboo ecosystem itself to strengthen narrative impact through contextual resonance. This study employed a practice-led research approach using a three-stage production workflow grounded in Visual Communication Design and Documentary Photography theories. Data were collected through immersive fieldwork and participatory observation to capture the authentic relationship between the community and bamboo in the context of Pasar Papringan. The resulting photobook applies distinct visual treatments across three chapters—monochrome, warm, and bright color schemes—to guide the audience’s emotional journey. The dissemination phase was implemented through an exhibition featuring interactive installations, including a bamboo-framed mirror, which successfully increased audience engagement. Shifts in public perception were assessed through qualitative intercept interviews with five exhibition visitors, evaluating three indicators: (1) expanded knowledge of bamboo’s history and cultural uses, (2) attitudinal change in how visitors valued bamboo as an aesthetic and cultural material, and (3) expressed motivation to support bamboo conservation or engage with bamboo-based initiatives. All five respondents demonstrated positive change on at least two indicators, with four explicitly reporting a changed or reinforced appreciation of bamboo’s cultural and economic significance. However, the amount of explanatory text required to fulfill academic standards was perceived as limiting accessibility for general audiences. The findings demonstrate that photobooks can function as an effective medium for cultural preservation and environmental awareness. This study also highlights the need for greater flexibility in practice-led research guidelines within educational institutions to better balance academic rigor with public communicative effectiveness